Association of Aquatic worms and infected snails with Digenean larvae (Baghdad Science Journal, 2015)
Six species of aquatic snails were sorted from three sites, the irrigation canal of Baghdad University campus (S1), River Tigris at Al-Za'afaraniah district / Baghdad(S2) , and River Euphrates at Al-Haideriah district Al-Najaf province(S2). The species included Melanopsis nodosa ;Melanoides tuberculata ; Thaiodaxsas jordani ; Lymnaea auricularia ; Physa acuta and Bellamya bengalensis. The first specis recorded the highest total number and was found in high density in the R. Euphrates site (S3), while the last species was the most widely distributed species, and found in all study sites. The last three species were found in Tigris river (S2) , while the first and last species were collected from the irrigation canal (S1).The result revealed that the species M. nodosa, M. tuberculata and L. auricularia were infected with Digenean larval stages, and the first species recorded the highest infection percentage of 60.04%, and the lowest percentage of 5.70% was recorded in L. auriculari , while M. tuberculata recorded a percentage of 38.98%.The oligochaetes Chaetogaster limnaei was sorted from the mantle cavity of L. auriculari and P. acuta, and it was noted that the first species accommodated more worms numbers than the second species. Twelve Species of family Naididae worms (subfamily Naidinae and subfamily Pristininae) , in addition to Aeolosoma leidyi of family Aeolosomatidae were sorted from the specific aquarium of each snail species. The leech Glossiphonia heteroclite was also recorded. The Nematodes worms were recorded the highest number sorted from the aquarium of L.auricularia, which are the most associate species, and 10 species of 49 individuals of worms were sorted from its aquarium, specially Dero ( Dero)digitata. In general, the infected snails, M. nodusa, M. tuberculata, and L. auricularia showed the highest association with worms, and from their aquaria 48, 37 , and 49 individuals of worms . with a number of 8,3, and 18 species respectively.